Shared hiking experiences: A phenomenological study of interactions in nature - Jonathan Joseph; Simone Grabowski; Najmeh Hassanli (Journal of Outdoor Recreation and Tourism, 2026)

Coastal resident's perceptions and attitudes of the visual impacts of oyster aquaculture cultivation methods along the Atlantic coast of the US - Kelsey M. Schultz; Steven B. Scyphers; A. Randall Hughes; David L. Kimbro; Stephen Kirk; Jonathan H. Grabowski (Ocean & Coastal Management, 2026)

Fishers' Local Ecological Knowledge Reveals Complex Food Web Dynamics With Rapidly Warming Waters - Loren McClenachan; Benjamin Neal; Marissa McMahan; Ellie Batchelder; Neida Villanueva‐Galarza; Jonathan Grabowski (Fish and Fisheries, 2025)
Local ecological knowledge (LEK) can provide insight into ecosystem change, particularly in dynamic ecological conditions, such as those driven by climate change. In New England lobster fisheries, warming waters have the potential to disrupt food webs, as range‐shifting species introduce novel ecological interactions. Here we use interviews with lobster fishers in Maine and Massachusetts to understand lobster fishers' LEK of dynamic food webs, taking a mental modelling approach to construct LEK food web models under rapidly warming waters. We find that fishers are observing a remarkable range of ecological interactions across habitats, collectively reporting knowledge of > 35 species that interact trophically with lobster across larval, juvenile, and adult life stages, ranging from terrestrial species like mink ( Neovison vison ) to deep sea species like redfish ( Sebastes fasciatus ). Our LEK food webs demonstrate perceptions of warming water altering species' abundances and interactions, with an overall negative impact on lobster fisheries. Fishers also report knowledge of complex interactions, including predation, competition, and habitat loss mediated by warming waters and changing species' abundances. Finally, we identify and categorise three main pathways that contribute to fishers' LEK, including observation, word of mouth, and inference. Our findings demonstrate that active fishers have complex understandings of food web interactions in dynamic ecosystems that are changing rapidly. With management unable to keep pace with climate‐driven change, fishers' LEK is an invaluable source of knowledge, whose use could improve the ability to understand the diverse impacts of warming waters on coastal ecosystems.

Assessing how restoration can facilitate 30×30 goals for climate‐resilient coastal ecosystems in the United States - Rachel K. Gittman; Christopher J. Baillie; Annick Cros; Jonathan H. Grabowski; Mary‐Margaret McKinney; Vienna R. Saccomanno; Carter. S. Smith; Bryan DeAngelis (Conservation Biology, 2025)
Ecosystems globally have reached critical tipping points because of climate change, urbanization, unsustainable resource consumption, and pollution. In response, international agreements have set targets for conserving 30% of global ecosystems and restoring 30% of degraded lands and waters by 2030 (30×30). In 2021, the United States set a target to jointly conserve and restore 30% of US lands and waters by 2030, with a specific goal to restore coastal ecosystems, namely wetlands, seagrasses, coral and oyster reefs, and mangrove and kelp forests, to increase resilience to climate change. Although US efforts to conserve and restore coastal ecosystems have increased in recent decades, critical knowledge gaps about the effectiveness of past and current efforts remain. To address key knowledge gaps, we first collated information on current and historic extent and drivers of change for wetlands, seagrasses, coral and oyster reefs, and mangrove and kelp forests in the United States. We then synthesized guiding principles from the literature for restoration practitioners to evaluate ecosystem trade‐offs, sustain and enhance ecosystem connectivity, bolster climate resilience, and promote social equity. Significant investment in standardized ecosystem mapping and monitoring and multispecies, landscape‐scale restoration efforts can improve resilience of coastal ecosystems to climate change and help the United States achieve its 30×30 target.

Multi‐endmember mixing and primary productivity drive carbonate system variability on a highly heterogeneous, shallow productive bank - F. Dylan Titmuss; Jennie E. Rheuban; Louise P. Cameron; Jonathan H. Grabowski; Zhaohui Aleck Wang (Limnology and Oceanography, 2025)
This study presents the first high‐resolution spatial analysis of carbonate chemistry on Georges Bank, a highly productive shallow bank located at the southeastern edge of the Gulf of Maine. Despite numerous studies on the hydrography, nutrient chemistry, and biology, regional carbonate chemistry remains unexplored, in particular for near‐bottom conditions. Observations from cruises in May and October 2021 were used to identify multi‐endmember mixing, and a Bayesian mixing model was applied to temperature and salinity to separate water mass mixing from non‐conservative drivers such as net community production, air–sea exchange, and other biogeochemical processes/errors. Major findings from this study indicate that carbonate chemistry is highly heterogeneous and driven by multi‐endmember mixing, although biological production and respiration were notable while air–sea CO 2 exchange was minimal. Five water masses with unique carbonate chemistry were observed that varied by season and with depth, showing complexity that is uncommon in other regions along the US Atlantic coast. In both cruises, a Warm Slope Water intrusion was identified at depth that contained a strong signal of CaCO 3 dissolution during the October cruise, observed in situ for the first time in this region. Under a high emissions scenario, our results suggest that much of the bank's bottom waters may become undersaturated with respect to aragonite by 2100. Together, these findings suggest that the in situ dissolution observed may only worsen with future ocean acidification, with potentially significant implications for ecologically and economically important shellfish species on Georges Bank.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Observations, perceptions and concerns of the American lobster industry regarding the range-expansion of Black Sea Bass - Helen Cheng; Marissa D. McMahan; Steven B. Scyphers; Loren McClenachan; Jonathan H. Grabowski (Marine Policy, 2025)

Natural and fishing disturbances combine to drive seafloor conservation outcomes from spatial closures on Georges Bank - Bradley P. Harris; Suresh A. Sethi; Felipe Restrepo; Jonathan H. Grabowski; Kevin Stokesbury (Biological Conservation, 2025)

Estimation of Nekton Density and Production Enhancement from Seagrass Nursery Habitats Along Regions of the U.S. Atlantic Coast - Philine S. E. zu Ermgassen; Bryan DeAngelis; Jonathan R. Gair; Sophus O.S.E. zu Ermgassen; Ronald Baker; Juhyung Lee; Timothy C. MacDonald; Kara Meckley; Marta Ribera; Jonathan H. Grabowski (Estuaries and Coasts, 2025)
Seagrass beds are designated as essential fish habitat by the National Oceanic and Atmospheric Administration (NOAA) and the regional fishery management councils due to their critical role as nurseries for nekton. Yet, they face significant threats globally and have suffered substantial declines in extent and habitat quality. Quantitative estimates of the degree to which seagrasses enhance nekton productivity can help inform conservation and management measures and assist in communicating the critical role of these threatened coastal habitats. In this study, juvenile fish and mobile macroinvertebrate (nekton) density data were compiled from seagrass and nearby unstructured habitats for both the Atlantic coast of South Florida and the Mid-Atlantic regions of the USA. Based on these field data, species that were consistently enhanced in seagrass habitats were identified. The annual production resulting from the identified juvenile enhancement by seagrasses was then estimated using an existing methodology based on established growth and mortality relationships for each species. Seagrasses enhanced nekton production by an additional 218.0 [SD 48.0] g m −2 year −1 (17 enhanced species) and 126.8 [SD 34.8] g m −2 year −1 (nine enhanced species) in the Atlantic coast of South Florida and the Mid-Atlantic regions, respectively. Data limitations resulted in only 54% and 44% of recorded species being assessed in the two regions, respectively, indicating that the current estimates are likely a substantial underestimate of the true nekton production enhancement. These estimates nevertheless provide a first quantitative assessment of seagrass enhancement of nekton production on the U.S. Atlantic coast, which can be built on as more data become available.

Addressing constraints to shellfish aquaculture through quantifying public perceptions and attitudes along the Atlantic coast of the US - Kelsey M. Schultz; Steven B. Scyphers; A. Randall Hughes; David L. Kimbro; Stephen Kirk; Jonathan H. Grabowski (Ocean & Coastal Management, 2024)

Nonconsumptive effects of black sea bass (Centropristis striata) on a crustacean mesopredator and the indirect effects on bivalve survival - Stephen M. Heck; Christopher J. Paparo; Amanda I. Tinoco; Tracey J. Vlasak; Brianna V. Cahill; Stephen V. Milea; Kaitlyn A. O'Toole; Brittney J. Scannell; Jonathan H. Grabowski; Bradley J. Peterson (Journal of Experimental Marine Biology and Ecology, 2024)

Effects of elevated pCO 2 and temperature on the calcification rate, survival, extrapallial fluid chemistry, and respiration of the Atlantic Sea scallop Placopecten magellanicus - Louise P. Cameron; Jonathan H. Grabowski; Justin B. Ries (Limnology and Oceanography, 2022)
Anthropogenic CO 2 ‐emission is causing ocean warming and acidification. Understanding how basic physiological processes of marine organisms respond to these stressors is important for predicting their responses to future global change. We examined the effects of elevated pCO 2 and temperature (pCO 2 = 344–2199 ppm; temperature = 6°C, 9°C, and 12°C) on the calcification rate, extrapallial fluid (EPF) carbonate chemistry, respiration, and survivorship of Atlantic sea scallops ( Placopecten magellanicus ) in a fully crossed 143‐d experiment. Rates of calcification and respiration were inhibited by elevated pCO 2 , and mortality occurred when elevated pCO 2 was accompanied by high‐temperature stress. Declines in growth and survivorship were likely caused by external shell dissolution, thermal stress, and hypercapnic reduction of metabolism under elevated pCO 2 . Concentrations of dissolved inorganic carbon (DIC) and total alkalinity in the EPF increased above seawater concentrations in response to elevated pCO 2 . EPF pH declined, but did not decline as much as seawater pH, indicating that scallops regulate EPF pH to support calcification. The combination of EPF pH regulation and DIC elevation yielded an increase in EPF [] under elevated pCO 2 treatments. The combination of low respiration rates, high EPF [], and low calcification rates under elevated pCO 2 suggests that the impaired calcification arises more from hypercapnic inhibition of metabolic activity and external shell dissolution than from chemically unfavorable conditions in the EPF. These results demonstrate the importance of EPF chemistry for bivalve biomineralization, but show that regulation efforts are insufficient to fully offset the deleterious effects of elevated pCO 2 on scallop performance.

Estimating and Applying Fish and Invertebrate Density and Production Enhancement from Seagrass, Salt Marsh Edge, and Oyster Reef Nursery Habitats in the Gulf of Mexico - Philine S. E. zu Ermgassen; Bryan DeAngelis; Jonathan R. Gair; Sophus zu Ermgassen; Ronald Baker; Andre Daniels; Timothy C. MacDonald; Kara Meckley; Sean Powers; Marta Ribera; Lawrence P. Rozas; Jonathan H. Grabowski (Estuaries and Coasts, 2021)
Seagrasses, oyster reefs, and salt marshes are critical coastal habitats that support high densities of juvenile fish and invertebrates. Yet which species are enhanced through these nursery habitats, and to what degree, remains largely unquantified. Densities of young-of-year fish and invertebrates in seagrasses, oyster reefs, and salt marsh edges as well as in paired adjacent unstructured habitats of the northern Gulf of Mexico were compiled. Species consistently found at higher densities in the structured habitats were identified, and species-specific growth and mortality models were applied to derive production enhancement estimates arising from this enhanced density. Enhancement levels for fish and invertebrate production were similar for seagrass (1370 [SD 317] g m –2 y –1 for 25 enhanced species) and salt marsh edge habitats (1222 [SD 190] g m –2 y –1 , 25 spp.), whereas oyster reefs produced ~650 [SD 114] g m –2 y –1 (20 spp). This difference was partly due to lower densities of juvenile blue crab ( Callinectes sapidus ) on oyster reefs, although only oyster reefs enhanced commercially valuable stone crabs ( Menippe spp.). The production estimates were applied to Galveston Bay, Texas, and Pensacola Bay, Florida, for species known to recruit consistently in those embayments. These case studies illustrated variability in production enhancement by coastal habitats within the northern Gulf of Mexico. Quantitative estimates of production enhancement within specific embayments can be used to quantify the role of essential fish habitat, inform management decisions, and communicate the value of habitat protection and restoration.

Geographic Variation in Life-History Traits of Black Sea Bass (Centropristis striata) During a Rapid Range Expansion - Marissa D. McMahan; Graham D. Sherwood; Jonathan H. Grabowski (Frontiers in Marine Science, 2020)

Regional environmental variation and local species interactions influence biogeographic structure on oyster reefs - Jonathan H. Grabowski; Tarik C. Gouhier; James E. Byers; Luke F. Dodd; A. Randall Hughes; Michael F. Piehler; David L. Kimbro (Ecology, 2020)
Although species interactions are often assumed to be strongest at small spatial scales, they can interact with regional environmental factors to modify food web dynamics across biogeographic scales. The eastern oyster ( Crassostrea virginica ) is a widespread foundational species of both ecological and economic importance. The oyster and its associated assemblage of fish and macroinvertebrates is an ideal system to investigate how regional differences in environmental variables influence trophic interactions and food web structure. We quantified multiple environmental factors, oyster reef properties, associated species, and trophic guilds on intertidal oyster reefs within 10 estuaries along 900 km of the southeastern United States. Geographical gradients in fall water temperature and mean water depth likely influenced regional (i.e., the northern, central and southern sections of the SAB) variation in oyster reef food web structure. Variation in the biomass of mud crabs, an intermediate predator, was mostly (84.1%) explained by reefs within each site, and did not differ substantially among regions; however, regional variation in the biomass of top predators and of juvenile oysters also contributed to biogeographic variation in food web structure. In particular, region explained almost half (40.2%) of the variation in biomass of predators of blue crab, a top predator that was prevalent only in the central region where water depth was greater. Field experiments revealed that oyster mortality due to predation was greatest in the central region, suggesting spatial variation in the importance of trophic cascades. However, high oyster recruitment in the middle region probably compensates for this enhanced predation, potentially explaining why relatively less variation (17.9%) in oyster cluster biomass was explained by region. Region also explained over half of the variation in biomass of mud crab predators (55.2%), with the southern region containing almost an order of magnitude more biomass than the other two regions. In this region, higher water temperatures in the fall corresponded with higher biomass of fish that consume mud crabs and of fish that consume juvenile and forage fish, whereas biomas of their prey (mud crabs and juvenile and forage fish, respectively) was generally low in the southern region. Collectively, these results show how environmental gradients interact with trophic cascades to structure food webs associated with foundation species across biogeographic regions.

Views from the dock: Warming waters, adaptation, and the future of Maine’s lobster fishery - Loren McClenachan; Steven Scyphers; Jonathan H. Grabowski (Ambio, 2020)

Shifting perceptions of rapid temperature changes’ effects on marine fisheries, 1945–2017 - Loren McClenachan; Jonathan H. Grabowski; Madison Marra; C. Seabird McKeon; Benjamin P. Neal; Nicholas R. Record; Steven B. Scyphers (Fish and Fisheries, 2019)
Climate‐driven warming has both social and ecological effects on marine fisheries. While recent changes due to anthropogenic global warming have been documented, similar basin‐wide changes have occurred in the past due to natural temperature fluctuations. Here, we document the effects of rapidly changing water temperatures along the United States’ east coast using observations from fisheries newspapers during a warming phase (1945–1951) and subsequent cooling phase (1952–1960) of the Atlantic Multidecadal Oscillation, which we compared to similar recent observations of warming waters (1998–2017). Historical warming and cooling events affected the abundance of species targeted by fishing, the prevalence of novel and invasive species, and physical access to targeted species. Fishing communities viewed historical cooling waters twice as negatively as they did warming waters (72% vs. 35% of observations). Colder waters were associated with a decrease in fishing opportunity due to storminess, while warming waters were associated with the potential for new fisheries. In contrast, recent warming waters were viewed as strongly negative by fishing communities (72% of observations), associated with disease, reductions in abundances of target species, and shifts in distributions across jurisdictional lines. This increasing perception that warming negatively affects local fisheries may be due to an overall reduction of opportunity in fisheries over the past half century, an awareness of the relative severity of warming today, larger changes in American culture, or a combination of these factors. Negative perceptions of recent warming waters’ effects on fisheries suggest that fishing communities are currently finding the prospect of climate adaptation difficult.

Voluntary Restoration: Mitigation's Silent Partner in the Quest to Reverse Coastal Wetland Loss in the USA - Rachel K. Gittman; Christopher J. Baillie; Katie K. Arkema; Richard O. Bennett; Jeff Benoit; Seth Blitch; Julien Brun; Anthony Chatwin; Allison Colden; Alyssa Dausman; Bryan DeAngelis; Nathaniel Herold; et al. (Frontiers in Marine Science, 2019)

Invasion dynamics: interactions between the European Green Crab Carcinus maenas and the Asian Shore Crab Hemigrapsus sanguineus - Christopher Baillie; Jonathan H. Grabowski (Biological Invasions, 2019)

Maximizing the benefits of oyster reef restoration for finfish and their fisheries - Ben L. Gilby; Andrew D. Olds; Charles H. Peterson; Rod M. Connolly; Christine M. Voss; Melanie J. Bishop; Michael Elliott; Jonathan H. Grabowski; Nicholas L. Ortodossi; Thomas A. Schlacher (Fish and Fisheries, 2018)
Global declines in oyster reefs have resulted in reduced habitat heterogeneity, extent and quality for some coastal finfish, potentially reducing fish populations and catches. It is well established that habitat restoration results in higher finfish biomass and diversity where oyster reefs replace bare substrata. Therefore, restoring oyster reefs with a view to also improving fish stocks is often a key goal of oyster restoration. However, the principles of habitat quality, ecological connectivity and broader ecosystem management are poorly integrated within oyster reef restoration ecology, but such principles may be instructive in enhancing the benefits of projects on fish populations throughout estuarine seascapes. This manuscript presents a framework for projects seeking to restore both oyster reef habitat and finfish communities. Structurally and biologically complex oyster reefs, comprising both oysters and other invertebrates, are required to provide shelter, food and nursery services to fish. By carefully considering site selection at seascape scales (km to 10s of km), restoration can enhance the network of habitat available to fish and potentially increase the overall carrying capacity of the estuary. Managers of estuaries that now include restored oyster reefs should implement fisheries management plans and consider the effects of management actions broadly throughout catchments; failing to do so may jeopardize gains in fish yields. Management decisions must be adaptable, responding to key criteria in thorough monitoring programs. Integrating these ecological and coastal management concepts into oyster reef restoration will enhance outcomes for fishes and increase stakeholder engagement and cost‐effectiveness.

Competitive and agonistic interactions between the invasive Asian shore crab and juvenile American lobster - Christopher J. Baillie; Jonathan H. Grabowski (Ecology, 2018)
Invasive species can have profound ecological and evolutionary impacts on native fauna, particularly those from overlapping guilds. Intraguild predation and competition often occur simultaneously, and ontogenetic shifts in competitive strength can dictate the magnitude and direction of species interactions. The recent introduction of the Asian shore crab Hemigrapsus sanguineus to the Atlantic coast of North America has resulted in the potential for considerable intraguild interactions with juvenile American lobsters Homarus americanus , with which it now co‐occupies rocky intertidal and shallow subtidal habitats. We present data from 5 yr of monthly (May–October) field sampling revealing a significant decline in lobster density as H. sanguineus density increased in the low intertidal. To investigate potential mechanisms behind this pattern, we conducted three mesocosm experiments designed to examine whether competitive interactions between H. americanus and H. sanguineus are size‐ or density‐dependent. Larger early benthic phase lobsters (16–34 mm CL ) outcompeted H. sanguineus for both food and shelter resources. These lobsters fed faster and more in the presence of H. sanguineus , effectively defended shelter, were responsible for the majority of agonistic interactions, and, in multiple instances, killed and consumed H. sanguineus . Effects on sheltering and agonstic interactions by these lobsters were independent of H. sanguineus density; however, prior shelter residency increased lobster agonistic behavior towards crabs. In contrast, H. sanguineus outcompeted smaller, early benthic phase lobsters (7.2–11.2 mm CL ) for shelter, and these interactions were density dependent. Displacement of lobsters from shelter by crabs and cumulative agonistic interactions instigated by crabs towards lobsters scaled positively with H. sanguineus density. Given the similarity of the invasion documented here and others occurring globally, these experiments demonstrate the importance of considering how factors such as ontogeny, density‐dependence, and primacy influence the outcomes of interactions between intraguild predators. Disentangling how these factors structure intraguild interactions between invasive and endemic species will both advance our fundamental understanding of community ecology and enhance efforts to conserve and manage natural resources.

Habitat Associations of Juvenile Cod in Nearshore Waters - Jonathan H. Grabowski; Christian W. Conroy; Rachel K. Gittman; Joseph T. Kelley; Sally Sherman; Graham D. Sherwood; Gail Wippelhauser (Reviews in Fisheries Science & Aquaculture, 2018)

Threat of Predation Does Not Affect Crassostrea virginica Filtration - Luke F. Dodd; Joseph C. Caracappa; Stephen R. Fegley; Jonathan H. Grabowski; Michael F. Piehler (Estuaries and Coasts, 2018)

Nonconsumptive effects of a predator weaken then rebound over time - David L. Kimbro; Jonathan H. Grabowski; A. Randall Hughes; Michael F. Piehler; J. Wilson White (Ecology, 2017)
Predators can influence prey traits and behavior (nonconsumptive effects [ NCEs ]), often with cascading effects for basal resources and ecosystem function. But critiques of NCE experiments suggest that their duration and design produce results that describe the potential importance of NCE s rather than their actual importance. In light of these critiques, we re‐evaluated a toadfish (predator), crab (prey), and oyster (resource) NCE ‐mediated trophic cascade. In a 4‐month field experiment, we varied toadfish cue ( NCE ) and crab density (approximating variation in predator consumptive effects, CE ). Toadfish initially benefitted oyster survival by causing crabs to reduce consumption. But this NCE weakened over time (possibly due to prey hunger), so that after 2 months, crab density ( CE ) dictated oyster survivorship, regardless of cue. However, the NCE ultimately re‐emerged on reefs with a toadfish cue, increasing oyster survivorship. At no point did the effect of toadfish cue on mud crab foraging behavior alter oyster population growth or sediment organic matter on the reef, which is a measure of benthic‐pelagic coupling. Instead, both decreased with increasing crab density. Thus, within a system shown to exhibit strong NCE s in short‐term experiments (days) our study supported predictions from theoretical models: (a) within the generation of individual prey, the relative influence of NCE s appears to cycle over longer time periods (months); and (b) predator CE s, not NCE s, drive longer‐term resource dynamics and ecosystem function. Thus, our study implies that the impacts of removing top predators via activities such as hunting and overfishing will cascade to basal resources and ecosystem properties primarily through density‐mediated interactions.

Refuge quality impacts the strength of nonconsumptive effects on prey - Sarah C. Donelan; Jonathan H. Grabowski; Geoffrey C. Trussell (Ecology, 2017)
Prey often retreat into the safety of refuges for protection from predators. This shift into refuge can reduce foraging opportunities, escalating the costs of risk and the strength of nonconsumptive effects. Such costs, however, may be shaped by the variation in resources that refuges harbor for prey foraging (i.e., refuge quality), and change dynamically via impacts on prey state. Despite its potential importance, we lack an explicit understanding of how refuge quality impacts prey performance under risk. Using a rocky intertidal food chain, we examined the interaction between predation risk and the amount of resources available for prey in refuge. We found that refuges with more resources greatly reduce the costs of refuge use, and that nonconsumptive effects are thereby weakened by as much as one‐half, with especially strong impacts on prey growth and growth efficiency. These results suggest that failure to consider refuge quality could result in overestimation of the negative effects associated with prey refuge use.

Predators, environment and host characteristics influence the probability of infection by an invasive castrating parasite - Alyssa-Lois M. Gehman; Jonathan H. Grabowski; A. Randall Hughes; David L. Kimbro; Michael F. Piehler; James E. Byers (Oecologia, 2017)

Measuring individuality in habitat use across complex landscapes: approaches, constraints, and implications for assessing resource specialization - F. Joel Fodrie; Lauren A. Yeager; Jonathan H. Grabowski; Craig A. Layman; Graham D. Sherwood; Matthew D. Kenworthy (Oecologia, 2015)

Geographic variation in intertidal oyster reef properties and the influence of tidal prism - James E. Byers; Jonathan H. Grabowski; Michael F. Piehler; A. Randall Hughes; Heidi W. Weiskel; Jennafer C. Malek; David L. Kimbro (Limnology and Oceanography, 2015)
Physical‐biological coupling helps structure aquatic communities, yet physical factors can vary widely across large, biogeographic scales. The eastern oyster ( Crassostrea virginica ) is an ecosystem engineer that creates intertidal reefs, filters water, promotes denitrification, stabilizes shorelines, and provides habitat throughout the inner waters of the U.S. South Atlantic Bight (SAB). We quantified physical variables (temperature, salinity, duration and depth of water inundation), oyster reef properties (slope, vertical relief), and oyster recruitment, density, and biomass over a 1500 km scale across the SAB for one year. All oyster‐level and many reef‐level variables exhibited unimodal patterns with latitude that peaked in Georgia and South Carolina estuaries. Of the physical variables, salinity and duration of water inundation over reefs were similar across all sites, and temperature declined linearly with increasing latitude, except during summer when it had no relationship with latitude. Depth of water inundation over reefs was the only physical variable with a prominent unimodal distribution that may explain the oyster's biological responses. Similar durations of water inundation across all reefs coupled with higher water depths in the mid‐latitude sites collectively indicate that these sites experience higher flow velocity, energy and net water volume delivery per unit time. The resultant higher accumulation of oyster biomass and heightened reef structure in areas of higher tidal energy emphasize that the physical forcing of the SAB (especially large cross‐shelf gradients in tidal amplification) affects the biology of the eastern oyster, including its reef properties, with potential implications for community structure and ecosystem service delivery across a biogeographic scale.

The biogeography of trophic cascades on US oyster reefs - David L. Kimbro; James E. Byers; Jonathan H. Grabowski; A. Randall Hughes; Michael F. Piehler (Ecology Letters, 2014)
Predators can indirectly benefit prey populations by suppressing mid‐trophic level consumers, but often the strength and outcome of trophic cascades are uncertain. We manipulated oyster reef communities to test the generality of potential causal factors across a 1000‐km region. Densities of oyster consumers were weakly influenced by predators at all sites. In contrast, consumer foraging behaviour in the presence of predators varied considerably, and these behavioural effects altered the trophic cascade across space. Variability in the behavioural cascade was linked to regional gradients in oyster recruitment to and sediment accumulation on reefs. Specifically, asynchronous gradients in these factors influenced whether the benefits of suppressed consumer foraging on oyster recruits exceeded costs of sediment accumulation resulting from decreased consumer activity. Thus, although predation on consumers remains consistent, predator influences on behaviour do not; rather, they interact with environmental gradients to cause biogeographic variability in the net strength of trophic cascades.

Assessing the Vulnerability of Marine Benthos to Fishing Gear Impacts - Jonathan H. Grabowski; Michelle Bachman; Chad Demarest; Steve Eayrs; Bradley P. Harris; Vincent Malkoski; David Packer; David Stevenson (Reviews in Fisheries Science & Aquaculture, 2014)

Host and parasite recruitment correlated at a regional scale - James E. Byers; Tanya L. Rogers; Jonathan H. Grabowski; A. Randall Hughes; Michael F. Piehler; David L. Kimbro (Oecologia, 2014)

The cost of safety: Refuges increase the impact of predation risk in aquatic systems - John L. Orrock; Evan L. Preisser; Jonathan H. Grabowski; Geoffrey C. Trussell (Ecology, 2013)
Although use of refuge habitats by prey can reduce their risk of predation, refuge use may also involve costs such as increased within‐refuge competition for resources. Despite the ubiquity of refuge use by prey, it is unknown whether predator‐induced use of refuges has widespread, negative nonconsumptive effects on prey growth, survival, and fecundity. We performed a meta‐analysis of 204 studies of aquatic taxa containing data on 271 distinct predator–prey pairs and found strong evidence that the negative effect of predation risk on prey activity, growth, and fecundity increases when prey have access to refuge habitats. Moreover, the effect of refuge habitats on growth and activity depends upon whether the refuge provides partial or total protection from predators. These results suggest that prey choosing whether to use refuges face a trade‐off between lowering the immediate risk of being consumed and increased nonconsumptive costs of refuge use. Our results suggest that changes in nonconsumptive effects in the presence of refuge habitats may alter prey population dynamics, coexistence, and metapopulation dynamics. Moreover, our results reveal key pragmatic considerations: the magnitude and direction of nonconsumptive effects may depend on the presence of refuge habitat and whether the refuge provides partial or total protection from predators.

Resource dynamics influence the strength of non‐consumptive predator effects on prey - Evan L. Preisser; Daniel I. Bolnick; Jonathan H. Grabowski (Ecology Letters, 2009)
Predators influence prey populations both by consuming individual prey, and by inducing changes in prey behaviour that limit reproduction and survival. Because prey trade‐off predation risk for forageing gains, the magnitude of predators’ non‐consumptive effects should depend on resource availability. Studies of non‐consumptive effects generally adopt either of two strategies: (i) maintaining a static ration of the prey’s resources; and (ii) using resource populations that vary dynamically in response to prey behaviour. Contrasting these experimental designs using meta‐analysis, we evaluated whether resource dynamics influence the magnitude of non‐consumptive effects on prey growth, survival, fecundity, population density, forageing rate and habitat use. Predators had a more negative effect on prey demography in dynamic‐ vs. static‐resource experiments. Our results highlight the importance of resource dynamics in mediating the magnitude of non‐consumptive effects of predators on prey, and illustrate the often‐unintended impacts of experimental design on estimates of effect size in ecological interactions.

The role of food limitation in lobster population dynamics in coastal Maine, United States, and New Brunswick, Canada - Jonathan H. Grabowski; Julien Gaudette; Erika J. Clesceri; Philip O. Yund (New Zealand Journal of Marine and Freshwater Research, 2009)
Lobster ( Homarus americanus ) landings in Maine, United States have increased steadily over the past two decades to levels that are consistently more than triple the 40‐year (1950 to 1990) annual average of c. 9000 MT. Meanwhile, the use of herring ( Clupea harengus ) as bait has increased fourfold since the 1970s, and is currently subsidising lobster productivity in mid‐coast Maine by augmenting the diet and growth of large juvenile and young adult lobsters before they recruit to the fishery. We investigated whether herring bait in the eastern portions of the Gulf of Maine is also subsidising these lobster populations. In 2004, we compared stomach contents, tissue production via stable isotope ratios, and growth rates of lobsters from seasonally open (Cutler, Maine, United States) and closed (Dipper Harbour, New Brunswick, Canada) fishing areas in the spring, summer, and autumn. Contrary to previous results in mid‐coast Maine, lobsters from seasonally closed sites at Dipper Harbour outgrew those from fished sites around Cutler. Yet examination of the diet of lobsters revealed several differences between open and closed sites that did not exist at sites in mid‐coast Maine. For instance, lobsters at Dipper Harbour consumed markedly more bivalves than those at Cutler. Furthermore, quantification of trap densities and the number of licensed fishers in mid‐coast versus eastern Maine determined that fishing effort was greatly reduced in eastern Maine. Thus, our results indicate thatherring bait subsidies are not important in eastern portions of the Gulf of Maine, but the availability of natural prey seemingly limits the growth of lobsters in eastern Maine. Moreover, our study suggests that bottom‐up forcing (i.e., food limitation) can have important consequences for lobster population dynamics and the productivity of lobster fisheries.

HABITAT COMPLEXITY INFLUENCES CASCADING EFFECTS OF MULTIPLE PREDATORS - Jonathan H. Grabowski; A. Randall Hughes; David L. Kimbro (Ecology, 2008)
Although multiple predator effects and trophic cascades have both been demonstrated in a wide variety of ecosystems, ecologists have yet to incorporate these studies into an experimental framework that also manipulates a common and likely important factor, spatial heterogeneity. We manipulated habitat complexity, the presence of two top predators (toadfish and blue crabs), and one intermediate predator (mud crabs) to determine whether habitat complexity influences the strength of multiple predator interactions across multiple trophic levels in experimental oyster reef communities. In the absence of toadfish, blue crabs caused significant mud crab mortality. Despite also directly consuming mud crabs, toadfish indirectly benefited this intermediate predator by decreasing blue crab consumption of mud crabs. Toadfish suppression of mud crab foraging activity, and thus decreased mud crab encounters with blue crabs, is likely responsible for this counterintuitive result. Contrary to previous investigations which suggest that more complex habitats reduce interference interactions among predators, reef complexity strengthened emergent multiple predator effects (MPEs) on mud crabs. The degree to which these MPEs cascaded down to benefit juvenile oysters (basal prey) depended on both habitat complexity and nonconsumptive effects derived from predator–predator interactions. Habitat complexity reduced the foraging efficiency of each crab species individually but released crab interference interactions when together, so that the two crabs collectively consumed more oysters on complex reefs. Regardless of reef complexity, toadfish consistently decreased consumption of oysters by both crab species individually and when together. Therefore, interactions between predator identity and habitat complexity structure trophic cascades on oyster reefs. Furthermore, these cascading effects of multiple predators were largely mediated by nonconsumptive effects in this system.

REVISITING THE CLASSICS: CONSIDERING NONCONSUMPTIVE EFFECTS IN TEXTBOOK EXAMPLES OF PREDATOR–PREY INTERACTIONS - Barbara L. Peckarsky; Peter A. Abrams; Daniel I. Bolnick; Lawrence M. Dill; Jonathan H. Grabowski; Barney Luttbeg; John L. Orrock; Scott D. Peacor; Evan L. Preisser; Oswald J. Schmitz; Geoffrey C. Trussell (Ecology, 2008)
Predator effects on prey dynamics are conventionally studied by measuring changes in prey abundance attributed to consumption by predators. We revisit four classic examples of predator–prey systems often cited in textbooks and incorporate subsequent studies of nonconsumptive effects of predators (NCE), defined as changes in prey traits (e.g., behavior, growth, development) measured on an ecological time scale. Our review revealed that NCE were integral to explaining lynx–hare population dynamics in boreal forests, cascading effects of top predators in Wisconsin lakes, and cascading effects of killer whales and sea otters on kelp forests in nearshore marine habitats. The relative roles of consumption and NCE of wolves on moose and consequent indirect effects on plant communities of Isle Royale depended on climate oscillations. Nonconsumptive effects have not been explicitly tested to explain the link between planktonic alewives and the size structure of the zooplankton, nor have they been invoked to attribute keystone predator status in intertidal communities or elsewhere. We argue that both consumption and intimidation contribute to the total effects of keystone predators, and that characteristics of keystone consumers may differ from those of predators having predominantly NCE. Nonconsumptive effects are often considered as an afterthought to explain observations inconsistent with consumption‐based theory. Consequently, NCE with the same sign as consumptive effects may be overlooked, even though they can affect the magnitude , rate, or scale of a prey response to predation and can have important management or conservation implications. Nonconsumptive effects may underlie other classic paradigms in ecology, such as delayed density dependence and predator‐mediated prey coexistence. Revisiting classic studies enriches our understanding of predator–prey dynamics and provides compelling rationale for ramping up efforts to consider how NCE affect traditional predator–prey models based on consumption, and to compare the relative magnitude of consumptive and NCE of predators.

FROM INDIVIDUALS TO ECOSYSTEM FUNCTION: TOWARD AN INTEGRATION OF EVOLUTIONARY AND ECOSYSTEM ECOLOGY - Oswald J. Schmitz; Jonathan H. Grabowski; Barbara L. Peckarsky; Evan L. Preisser; Geoffrey C. Trussell; James R. Vonesh (Ecology, 2008)
An important goal in ecology is developing general theory on how the species composition of ecosystems is related to ecosystem properties and functions. Progress on this front is limited partly because of the need to identify mechanisms controlling functions that are common to a wide range of ecosystem types. We propose that one general mechanism, rooted in the evolutionary ecology of all species, is adaptive foraging behavior in response to predation risk. To support our claim, we present two kinds of empirical evidence from plant‐based and detritus‐based food chains of terrestrial and aquatic ecosystems. The first kind comes from experiments that explicitly trace how adaptive foraging influences ecosystem properties and functions. The second kind comes from a synthesis of studies that individually examine complementary components of particular ecosystems that together provide an integrated perspective on the link between adaptive foraging and ecosystem function. We show that the indirect effects of predators on plant diversity, plant productivity, nutrient cycling, trophic transfer efficiencies, and energy flux caused by consumer foraging shifts in response to risk are qualitatively different from effects caused by reductions in prey density due to direct predation. We argue that a perspective of ecosystem function that considers effects of consumer behavior in response to predation risk will broaden our capacity to explain the range of outcomes and contingencies in trophic control of ecosystems. This perspective also provides an operational way to integrate evolutionary and ecosystem ecology, which is an important challenge in ecology.

CONSUMPTIVE AND NONCONSUMPTIVE EFFECTS OF PREDATORS ON METACOMMUNITIES OF COMPETING PREY - John L. Orrock; Jonathan H. Grabowski; Jelena H. Pantel; Scott D. Peacor; Barbara L. Peckarsky; Andrew Sih; Earl E. Werner (Ecology, 2008)
Although predators affect prey both via consumption and by changing prey migration behavior, the interplay between these two effects is rarely incorporated into spatial models of predator–prey dynamics and competition among prey. We develop a model where generalist predators have consumptive effects (i.e., altering the likelihood of local prey extinction) as well as nonconsumptive effects (altering the likelihood of colonization) on spatially separated prey populations (metapopulations). We then extend this model to explore the effects of predators on competition among prey. We find that generalist predators can promote persistence of prey metapopulations by promoting prey colonization, but predators can also hasten system‐wide extinction by either increasing local extinction or reducing prey migration. By altering rates of prey migration, predators in one location can exert remote control over prey dynamics in another location via predator‐mediated changes in prey flux. Thus, the effect of predators may extend well beyond the proportion of patches they visit. In the context of prey metacommunities, predator‐mediated shifts in prey migration and mortality can shift the competition–colonization trade‐off among competing prey, leading to changes in the prey community as well as changes in the susceptibility of prey species to habitat loss. Consequently, native prey communities may be susceptible to invasion not only by exotic prey species that experience reduced amounts of mortality from resident predators, but also by exotic prey species that exhibit strong dispersal in response to generalist native predators. Ultimately, our work suggests that the consumptive and nonconsumptive effects of generalist predators may have strong, yet potentially cryptic, effects on competing prey capable of mediating coexistence, fostering invasion, and interacting with anthropogenic habitat alteration.

Habitat context influences predator interference interactions and the strength of resource partitioning - A. Randall Hughes; Jonathan H. Grabowski (Oecologia, 2006)